Finite element modelling of stresses and failure within plasma spray thermal barrier coating systems - Kyaw, Si Thu (2013)
Air plasma sprayed thermal barrier coating (APS TBC) systems are usually applied to engine components to reduce the temperature of the substrate and increase the efficiency of engines. However, failure of these coatings leads to oxidation and corrosion of the substrate. Therefore, a thorough understanding of the coating failure is necessary to predict the lifetime of coated components. This project has carried out stress analysis and prediction of subsequent failure of APS TBC systems associated with sintering of the TBC, oxidation of the bond coat (BC), substrate geometry, undulations at the coating interfaces and coating fracture toughness. Stress analysis is crucial for predicting TBC failure as stresses in the vicinity of the coating interfaces cause cracks and subsequent coating delamination.